Development of Assessment Instruments to Measure Collaboration and Responsibility Skills of Students in Physics Learning on Cased Method-Based - Rosidin, Undang; Sesunan, Feriansyah; Fitria, Della (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
This study aims to develop an assessment instrument to measure student collaboration and responsibility skills in the context of case-based physics learning that is valid, reliable, and practical. This type of research is called research development (R&D) using the 7 stages adapted from (Borg & Gall, 1989). Product validation was carried out to assess aspects of construction, substance, and language. The results of expert validation of the assessment instrument to measure collaboration and responsibility skills were 88.72% and 85.43%, with very valid criteria. Then, this assessment instrument was tested on 30 students and analyzed using the Rasch model. Based on the results of the test data analysis, we obtained that: (1) 14 items of the collaboration instrument and 9 items of the responsibility instrument were declared valid; (2) the reliability of the collaboration and responsibility skills assessment instrument was 0.82 and 0.71 with perfect and good criteria; and (3) the average value of the practicality test of the collaboration and responsibility skills assessment instrument was 90.72% and 91.80% with very high criteria.